A review on flavones targeting serine/threonine protein kinases for potential anticancer drugs. Issue 5 (1st March 2019) - Zhao, Lulu; Yuan, Xinyu; Wang, Jubo; Feng, Yifan; Ji, Fei; Li, Zhiyu; Bian, Jinlei
Graphical abstract: Abstract: Protein kinases have been important targets for antitumor targets due to their key roles in regulating multiple cell signaling pathways. Numerous compounds containing flavonoid scaffold as an indispensable anchor have been found to be potent inhibitors of protein kinases. Some of these flavonoids have been in clinical research as protein kinases inhibitors. Thus, the present review mainly focuses on the structural requirement for anticancer potential of flavone derivatives targeting several key serine/threonine protein kinases. This information may provide an opportunity to scientists of medicinal chemistry to design multi-functional flavone derivatives for the treatment of cancer.